The tobacco phosphatidylethanolamine-binding protein NtFT4 increases the lifespan of Drosophila melanogaster by interacting with the proteostasis network. - Känel, P.; Noll, G.A.; Schroedter, K.; Naffin, E.; Kronenberg, J.; Busswinkel, F.; Twyman, R.M.; Klämbt, C.; Prüfer, D. (Aging, 2022)
Proteostasis reflects the well-balanced synthesis, trafficking and degradation of cellular proteins. This is a fundamental aspect of the dynamic cellular proteome, which integrates multiple signaling pathways, but it becomes increasingly error-prone during aging. Phosphatidylethanolamine-binding proteins (PEBPs) are highly conserved regulators of signaling networks and could therefore affect aging-related processes. To test this hypothesis, we expressed PEPBs in a heterologous context to determine their ectopic activity. We found that heterologous expression of the tobacco (Nicotiana tabacum) PEBP NtFT4 in Drosophila melanogaster significantly increased the lifespan of adult flies and reduced age-related locomotor decline. Similarly, overexpression of the Drosophila ortholog CG7054 increased longevity, whereas its suppression by RNA interference had the opposite effect. In tobacco, NtFT4 acts as a floral regulator by integrating environmental and intrinsic stimuli to promote the transition to reproductive growth. In Drosophila, NtFT4 engaged distinct targets related to proteostasis, such as HSP26. In older flies, it also prolonged Hsp26 gene expression, which promotes longevity by maintaining protein integrity. In NtFT4-transgenic flies, we identified deregulated genes encoding proteases that may contribute to proteome stability at equilibrium. Our results demonstrate that the expression of NtFT4 influences multiple aspects of the proteome maintenance system via both physical interactions and transcriptional regulation, potentially explaining the aging-related phenotypes we observed.